INOVASI MEDIA DIGITAL STORY BOOK UNTUK MENINGKATKAN MAHARAH QIRA’AH BAHASA ARAB KELAS VII MTSN 3 JOMBANG - Mamluk Ahtul Hidayah; Amrini Shofiyani; Rina Dian Rahmawati; Zaki Ahmad Fauzan (STKIP Pesisir Selatan, 2026)
This study aims to develop an interactive Digital Story Book learning media to significantly enhance Arabic reading skills (maharah qirā’ah) among seventh-grade students at MTsN 3 Jombang. Reading skills play a crucial role but are often hindered by low interest and monotonous media. The research employed a Research and Development (R&D) method utilizing the comprehensive 4D model (Define, Design, Develop, and Disseminate). Data were systematically collected through initial observations, in-depth interviews, questionnaires, pre-tests, and post-tests to measure skill improvements. The results of the material expert validation obtained an outstanding feasibility score of 90.59%, while the media expert validation reached 96.00%, both categorized as highly feasible for implementation. Field trials indicated an overwhelmingly positive student response with a score of 97.53%, proving that the media is highly engaging, user-friendly, and effective. The paired sample t-test revealed a significant difference between pre-test (average 37.23) and post-test (average 89.97) results with a p-value < 0.05, confirming that the interactive Digital Story Book effectively improves Arabic reading skills.